"We are not pro-Russian, but…". Comparing Communication of Czech ANO Movement and Slovak SMER-SD Regarding the Russian Aggression Against Ukraine. - Ondřej Filipec; Petra Měšťánková (Revista UNISCI, 2024)
Russia's full-scale invasion of Ukraine in 2022 represented a significant change in the geopolitical situation in Central and Eastern Europe, which was almost immediately reflected in the communication of political parties and their leaders. The main aim of this article is to analyse the communication of two populist parties: the Czech ANO movement of billionaire Andrej Babiš and the Slovak SMER-SD, mainly associated with its leader Robert Fico. Although both parties occupy important positions within the party systems of their respective countries and both are considered populist, they use different communication strategies and levels of pro-Russian orientation. The different communication strategies are analysed in the context of the electorate, inter-party relations, the coalition/opposition dichotomy and the personal influence of their leaders.